[Recensão a] Marcial, Epigramas. Edición de Rosario Moreno Soldevila y Alberto Marina Castillo. Madrid, Akal, 2019. 655 pp. ISBN 978-84-460-4700-1 - Pimentel, Maria Cristina (2022)
Recensão crítica a edição dos Epigramas de Marcial (Madrid, Akal).